2010
DOI: 10.5539/ijef.v2n3p163
|View full text |Cite
|
Sign up to set email alerts
|

Announcement Effects of Seasoned Equity Offerings in China

Abstract: By taking a longer period (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) this study examines the stock price reaction to the announcement of different equity issues in China. Initially, the study documents the announcement effects of Right issues and Public Offerings (SEOs). Secondly, it adds to the previous literature by keeping in view three successive announcement dates for SEOs as event dates i.e. Board of directors meeting date (BOD), shareholders' meeting date and announcement date to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
7
0
2
Order By: Relevance
“…There have been different studies on China’s public equity offerings. In contrast to our finding that the median CAR[−3,+3] for PEPs in China is 4.6%, Shahid et al () argue that the SEO’s announcement effect has a CAR[−3,+3] of −1.44% in China, while this negative market reaction to the SEO announcements is consistent with other prior studies in China (Cheung et al ; Fung et al ).…”
Section: Methodssupporting
confidence: 89%
“…There have been different studies on China’s public equity offerings. In contrast to our finding that the median CAR[−3,+3] for PEPs in China is 4.6%, Shahid et al () argue that the SEO’s announcement effect has a CAR[−3,+3] of −1.44% in China, while this negative market reaction to the SEO announcements is consistent with other prior studies in China (Cheung et al ; Fung et al ).…”
Section: Methodssupporting
confidence: 89%
“…The results showed that there were significant differences with the criteria <α (0.05), the hypothesis was accepted. The results of the study are the same as (Gajewski and Ginglinger, 2002;Shahid et al 2010) examining the event of the announcement of a right issue with the results of the study that abnormal returns differ significantly around the announcement of the right issue.…”
Section: Hypothesis Testingmentioning
confidence: 75%
“…Hypotheses Development. In the literature, the arising issues regarding market reactions following right issues can be generally classified into two main factions, namely short-term reactions (Ariff et al, 2007;Barnes and Walker, 2006;Feng et al, 2018;Iqbal, 2008;Krishnan et al, 2010;Paskelian and Bell, 2010;Shahid et al, 2010) and long-term reactions (Andrikopoulos, 2009;Bayless and Jay, 2008;Devos et al, 2017;Du et al, 2016;Dutta, 2017;Mansali and Daadaa, 2018;Silva and Bilinski, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%